Lithium iron phosphate borate positive electrode material and preparation method thereof, positive electrode plate and secondary battery

By introducing trivalent titanium and boron element doping into the lithium iron phosphate positive electrode material and using carbon cladding, the problems of low performance and high cost of lithium iron phosphate material are solved, and higher electrochemical performance and lower The production cost has enhanced the competitiveness of new energy vehicles.

CN119208594AActive Publication Date: 2024-12-27HUBEI WANRUN NEW ENERGY TECH CO LTD

Patent Information

Application Number
CN202411274106.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-27
Estimated Expiration
2044-09-11

AI Technical Summary

Technical Problem

The existing lithium iron phosphate positive electrode materials have low performance and high production costs, which affects the competitiveness of new energy vehicles.

Method used

Trivalent titanium is used for cation doping, boron element is anion doping, and carbon is used as a coating to form a lithium iron borate positive electrode material, reducing production costs through optimizing the process flow.

Benefits of technology

The ionic conductivity and capacity of lithium iron borate phosphate positive electrode material is improved, cycle stability is enhanced, production costs are reduced, and cost-effectiveness of new energy vehicles is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208594A_ABST
    Figure CN119208594A_ABST
Patent Text Reader

Abstract

The invention provides a lithium iron phosphate borate positive electrode material and a preparation method thereof, a positive electrode plate and a secondary battery, and belongs to the technical field of battery positive electrode materials, the chemical general formula of the lithium iron phosphate borate positive electrode material is LixFeTiyPzBwO (4z + 3w + 2y) / C, x, y, z and w are all non-zero positive numbers, 1.02 < = x < = 1.05, 0.01 < = y < = 0.05, 0.92 < = z < = 0.95, 0.05 < = w < = 0.15, based on the mass of the lithium iron phosphate borate positive electrode material being 100%, the sum of the total mass of the lithium iron phosphate borate positive electrode material is 100%, and the sum of the total mass of the lithium iron phosphate borate positive electrode material is 100%. And the mass content of C is 1.00%-1.35%. The lithium iron phosphate borate positive electrode material provided by the invention is low in price, excellent in ionic conductivity, high in capacity and excellent in rate capability, meanwhile, the cycling stability is further improved, and the lithium iron phosphate borate positive electrode material has a wider application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery positive electrode materials, and in particular to a lithium iron borate phosphate positive electrode material and a preparation method thereof, a positive electrode sheet and a secondary battery. Background Art

[0002] With the development of new energy vehicles, the competition is becoming increasingly fierce, and the requirements for cost performance are becoming higher and higher. New energy vehicles are required to have a long range and a low price. The cost of batteries in new energy vehicles generally accounts for more than 40%, and its cost performance directly determines the cost performance of new energy vehicles. The cost of positive electrode materials in batteries accounts for more than 30%. Therefore, reducing the cost of positive electrode materials and improving their performance can effectively enhance the competitiveness of new energy vehicles.

[0003] Lithium iron phosphate has an increasingly higher proportion as the positive electrode material of batteries in new energy vehicles due to its advantages such as low cost and high safety. How to continuously improve the performance of lithium iron phosphate and continuously reduce its production cost is the key to the steady development of lithium iron phosphate.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] In view of the technical problems existing in the background technology, the present application provides a lithium iron borate phosphate positive electrode material and its preparation method, a positive electrode plate and a secondary battery, aiming to solve the problems of low performance and high production cost of existing lithium iron phosphate positive electrode materials.

[0006] In the first aspect, the present invention provides a lithium boron phosphate positive electrode material, the lithium boron phosphate positive electrode material has a chemical formula of Li x FeTi y P z B w O (4z+3w+2y) / C, wherein x, y, z and w are all non-zero positive numbers, 1.02≤x≤1.05, 0.01≤y≤0.05, 0.92≤z≤0.95, 0.05≤w≤0.15, and based on the mass of the boric acid phosphate positive electrode material being 100%, the mass fraction of the carbon element is 1.00% to 1.35%.

[0007] The lithium iron borate phosphate positive electrode material provided in the embodiment of the present application is cation-doped with trivalent titanium and anion-doped with boron, and is coated with carbon. The ionic radius of trivalent titanium is larger and more defects are formed, thereby making the lithium iron borate phosphate positive electrode material have better ionic conductivity and higher capacity; the boron element is doped in the form of borate ions and the molar mass of borate is less than the molar mass of phosphate, which is beneficial to improving the capacity of the lithium iron borate phosphate positive electrode material; carbon as a coating layer is not only beneficial to improving the conductivity of the lithium iron borate phosphate positive electrode material, but also beneficial to improving the cycle stability.

[0008] In some embodiments, the D10 particle size of the lithium boron iron phosphate material is ≤0.5 μm, the D50 particle size is ≤1.60 μm, and the D90 particle size is ≤19.00 μm.

[0009] In this embodiment, the particle size of the lithium borate iron phosphate positive electrode material is more uniform, which is more conducive to improving the capacity and cycle stability of the battery prepared by using it as the positive electrode material.

[0010] In some embodiments, the pH value of the lithium iron borate phosphate positive electrode material is 8.50-9.00, which makes it easier to homogenize the positive electrode slurry in the subsequent preparation process, and is also more conducive to preparing a positive electrode sheet with uniform dispersion of the positive electrode material and stable performance.

[0011] In some embodiments, the compaction density of the lithium borate iron phosphate positive electrode material is 2.35 g / mL to 2.50 g / mL, and the specific surface area is 10.1 m 2 / g~14.3m 2 / g, powder resistivity is 4.0Ω.cm~13.0Ω.cm.

[0012] In this embodiment, the lithium iron borate phosphate positive electrode material has a higher compaction density, a larger specific surface area, and a lower powder resistivity, which is more conducive to improving the capacity of the battery formed using the lithium iron borate phosphate positive electrode material.

[0013] In some embodiments, the lithium boron iron phosphate positive electrode material has an iron dissolution of 3.0ppm to 10.0ppm, an elemental iron of 0.01ppm to 0.05ppm, a chloride ion of 40.0ppm to 80.0ppm, a water content of 280ppm to 350ppm, a free lithium of 140ppm to 200ppm, and a magnetic impurity content of ≤1ppm.

[0014] In this embodiment, the iron dissolution of the lithium borophosphate iron positive electrode material is ≤10.0ppm, the elemental iron is ≤0.05ppm, the chloride ion is ≤80.0ppm, the water content is ≤350ppm, the free lithium is ≤200ppm, and the magnetic impurity content is ≤1ppm. It has a stable structure and a low impurity content, which enables it to have more excellent ionic conductivity and cycle stability.

[0015] In the second aspect, an embodiment of the present application provides a method for preparing a lithium iron borate phosphate positive electrode material, which comprises the following steps: uniformly mixing a ferrous source, a trivalent titanium source, a carbon source, phosphoric acid, boric acid and a solvent to obtain a mixed slurry; preheating and drying the mixed slurry to obtain a pre-dried material; and calcining the pre-dried material to obtain a lithium iron borate phosphate positive electrode material.

[0016] In the technical scheme of the embodiment of the present application, lithium source, ferrous source, trivalent titanium source, carbon source, phosphoric acid, boric acid and solvent are used as raw materials, which is more conducive to enhancing the driving force of solid phase reaction, and it is easier to form a eutectic body. Compared with the dry mixing and calcining process, the reaction temperature is further reduced, the particles are further refined, the capacity is further improved, and the production cost is further reduced. At the same time, the ionic radius of the trivalent titanium ion is larger, and the defects formed are more, so that the ionic conductivity of the positive electrode material is better and the capacity is higher; the boron element is doped in the form of borate ions and the molar mass of the borate is less than the molar mass of the phosphate, which is conducive to improving the capacity; carbon as a coating layer is not only conducive to improving conductivity, but also conducive to improving cycle stability. In addition, compared with the traditional process, the above technical scheme reduces the steps of adding water slurry, grinding and spray drying. According to the statistics of actual production, the cost (including labor, equipment depreciation, energy consumption, environmental protection, etc.) is about 2500 yuan / ton. The preparation method of lithium iron borate phosphate positive electrode material provided in the present application can save 2,500 yuan / ton in this step alone. According to the annual production of 100,000 tons of lithium iron borate phosphate positive electrode material, the cost can be saved by 250 million yuan / year.

[0017] In some embodiments, the molar ratio of the iron element in the ferrous source, the titanium element in the trivalent titanium source, the lithium element in the lithium source, the carbon element in the carbon source, the phosphorus element in the phosphoric acid solution, and the boron element in the boric acid is 1: (0.01-0.05): (1.02-1.05): (0.36-1.32): (0.92-0.95): (0.05-0.15).

[0018] In this embodiment, the lithium iron borate phosphate positive electrode material obtained by the above molar ratio is cation-doped with trivalent titanium ions and anion-doped with boron elements, and is coated with carbon. The trivalent titanium ions have a larger ionic radius and form more defects, thereby making the lithium iron borate phosphate positive electrode material have better ionic conductivity and higher capacity; the boron element is doped in the form of borate ions and the molar mass of borate is less than the molar mass of phosphate, which is beneficial to improving the capacity, and boric acid has a fluxing effect, which is beneficial to obtaining a lithium iron borate phosphate positive electrode material with improved compaction density at a lower calcination temperature; carbon as a coating layer is not only beneficial to improving the ionic conductivity of the lithium iron borate phosphate positive electrode material, but also beneficial to improving the cycle stability.

[0019] In some specific embodiments, the step of mixing a lithium source, a ferrous source, a trivalent titanium source, a carbon source, phosphoric acid, boric acid and a solvent comprises: mixing phosphoric acid with a solvent to form a phosphoric acid solution, and then mixing the phosphoric acid solution with the lithium source, the ferrous source, the trivalent titanium source and boric acid. Preferably, the mass fraction of the phosphoric acid solution is 70%-80%, so as to improve the efficiency of uniform mixing of the phosphoric acid solution and other raw materials.

[0020] In some embodiments, the ferrous source is a water-soluble ferrous source, which includes at least one of ferrous acetate and / or ferrous chloride. The lithium source is a water-soluble lithium source, which includes at least one of lithium chloride and / or lithium acetate. At high temperatures, volatile anions combine with hydrogen ions in the acid to form volatile low-boiling acid, and then adopt the principle of preparing low-boiling acid with high-boiling acid, using high-boiling acid such as boric acid and phosphoric acid, mixed with chloride ions, acetate ions, etc., to form low-boiling hydrogen chloride and acetic acid, and other ions are combined together to form lithium iron borate phosphate. During the calcination process, the driving force of the solid phase reaction is stronger, and it is easier to form a eutectic body, which is conducive to reducing the calcination temperature, shortening the sintering time, and then reducing energy consumption and reducing costs, so that the lithium iron borate phosphate positive electrode material provided by the present application not only has a lower preparation method cost, a shorter process, but also has more refined particles and a higher capacity. At the same time, the boric acid introduced in the present application can be used as both a dopant and a flux, which can further reduce the calcination temperature and avoid the problem of increased particle size, iron phosphide and magnetic substance content of the lithium iron borate phosphate positive electrode material caused by high-temperature calcination, which is beneficial to the improvement of the electrochemical properties of the lithium iron borate phosphate positive electrode material in terms of capacity, cycle performance and rate performance.

[0021] In the present application, a trivalent titanium source is selected to provide titanium element. The trivalent titanium salt has a lower melting point (decomposition point) and can melt at a lower temperature, thereby enhancing the dispersion effect and making the trivalent titanium more uniformly doped in the lithium boroferric phosphate. In some embodiments, the trivalent titanium source includes titanium trihalide, preferably titanium trichloride, which can not only utilize the principle of preparing low-boiling acid with high-boiling acid to reduce the calcination reaction temperature, but also utilize the larger ionic radius of the trivalent titanium ion to form more defects during the doping process, which is beneficial to enhance the ionic conductivity of lithium ions, thereby improving the electrochemical performance of the lithium boroferric phosphate positive electrode material in terms of charge specific capacity, discharge specific capacity, etc.

[0022] In some embodiments, the carbon source is a water-soluble carbon source, and the water-soluble carbon source includes any one or more of ascorbic acid and citric acid. Preferably, the water-soluble carbon source is a mixture of ascorbic acid and citric acid, and the mass ratio of ascorbic acid to citric acid is (0.05-0.2): (0.92-0.95), which is more conducive to improving the conductivity and cycle stability of the lithium borate iron phosphate cathode material.

[0023] In some embodiments, the mixed slurry is preheated and dried at 100°C-150°C to obtain a pre-dried material having a mass fraction of H2O less than or equal to 0.5%. That is, in the preheating and drying process, the water content of the dried material is controlled to ≤0.5% after the water is removed, so that the product generated in the subsequent calcination process is more dense and uniform, thereby further improving the density of the lithium boric iron phosphate positive electrode material, which is beneficial to improving the compaction density and capacity of the lithium boric iron phosphate positive electrode material.

[0024] In some embodiments, the step of calcining the pre-dried material to obtain a lithium borophosphate iron positive electrode material includes: under a protective atmosphere, the pre-dried material is calcined at a first calcination temperature for a first insulation time, and then calcined at a second calcination temperature for a second insulation time to obtain the lithium borophosphate iron positive electrode material; wherein the first calcination temperature is 120°C-150°C, the first insulation time is 2h-4h, the second calcination temperature is 600°C-700°C, and the second insulation time is 4h-6h.

[0025] In this embodiment, controlling the first calcination temperature, the first insulation time, the second calcination temperature and the second insulation time is more conducive to preparing a lithium iron borate phosphate positive electrode material with finer and more uniform particles, more regular morphology and higher density, which is beneficial to improving the compaction density and capacity of the lithium iron borate phosphate positive electrode material.

[0026] In a third aspect, an embodiment of the present application provides a positive electrode plate, which includes the lithium iron borate phosphate positive electrode material provided in the first aspect.

[0027] In this embodiment, the positive electrode plate includes the above-mentioned lithium iron borate phosphate positive electrode material, which not only has higher compaction density and capacity, but also has better ion conductivity and cycle stability, and has broader application prospects in the field of secondary batteries.

[0028] In a fourth aspect, an embodiment of the present application provides a secondary battery, which includes the lithium iron borate phosphate positive electrode material provided in the first aspect or the positive electrode plate provided in the third aspect.

[0029] In this embodiment, the secondary battery includes the above-mentioned positive electrode plate, which not only has a high capacity but also has better ion conductivity and cycle stability.

[0030] In a fifth aspect, an embodiment of the present application provides an electrical device, which includes the lithium iron borate phosphate positive electrode material provided in the first aspect, the positive electrode plate provided in the third aspect, or the secondary battery provided in the fourth aspect.

[0031] In this embodiment, the electric device includes the secondary battery, and thus has the advantage of excellent cycle stability.

[0032] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0034] Figure 1 A flow chart for preparing the lithium iron borate phosphate positive electrode material provided in Example 1;

[0035] Figure 2 This is a scanning electron microscope (SEM) result image of the lithium borate iron phosphate positive electrode material provided in Example 1;

[0036] Figure 3 This is a SEM result of the lithium borate iron phosphate positive electrode material provided in Example 2;

[0037] Figure 4 This is a SEM result of the lithium iron borate phosphate positive electrode material provided in Example 3;

[0038] Figure 5 This is the SEM result of the lithium iron borate phosphate positive electrode material provided in Comparative Example 2. DETAILED DESCRIPTION

[0039] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0041] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0042] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0043] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0044] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0045] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.

[0046] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.

[0047] With the development of new energy vehicles, lithium iron phosphate positive electrode materials have become increasingly important as positive electrode materials in batteries used in new energy vehicles due to their low cost and high safety. However, existing lithium iron phosphate positive electrode materials still have problems with low performance and high production costs.

[0048] In order to solve the technical problems that the existing lithium iron phosphate positive electrode materials still have low performance and high production costs, the present application provides a lithium iron borate phosphate positive electrode material and its preparation method, positive electrode plate, secondary battery and power device, wherein the lithium iron borate phosphate positive electrode material is cation-doped with trivalent titanium and anion-doped with boron, and is coated with carbon at the same time. The ion radius of trivalent titanium is larger and more defects are formed, so that the ion conductivity of the positive electrode material is better and the capacity is higher; compared with phosphorus, the ion radius of boron is smaller, which is more conducive to improving the compaction density of the positive electrode material and thus improving the capacity; carbon as a coating layer is not only conducive to improving ion conductivity, but also conducive to improving cycle stability. Furthermore, the corresponding performance of the positive electrode plate, secondary battery and power device containing the lithium iron borate phosphate positive electrode material is also improved.

[0049] The electric device provided in the embodiment of the present application may be, but is not limited to, a mobile phone, a tablet, a laptop computer, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, etc. Among them, the electric toy may include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc., and the spacecraft may include an airplane, a rocket, a space shuttle, and a spacecraft, etc.

[0050] In a first aspect, the present invention provides a lithium borate phosphate cathode material having a general chemical formula of Li x FeTi y P z B w O (4z+3w+2y) / C, wherein x, y, z and w are all non-zero positive numbers, 1.02≤x≤1.05, 0.01≤y≤0.05, 0.92≤z≤0.95, 0.05≤w≤0.15, and based on the mass of the phosphate boric acid material being 100%, the mass fraction of the carbon element is 1.00% to 1.35%.

[0051] In the present application, the lithium iron borate phosphate positive electrode material includes a core and a coating layer coated on the outer surface of the core, wherein the chemical formula of the material of the core is: Li x FeTi y P z B w O (4z+3w+2y) , the material of the coating layer is carbon material.

[0052] The lithium iron borate phosphate positive electrode material provided in the embodiment of the present application is cation-doped with trivalent titanium and anion-doped with boron, and is coated with carbon. The ionic radius of trivalent titanium is larger and more defects are formed, thereby making the lithium iron borate phosphate positive electrode material have better ionic conductivity and higher capacity; the boron element is doped in the form of borate ions and the molar mass of borate is less than the molar mass of phosphate, which is beneficial to improving the capacity of the lithium iron borate phosphate positive electrode material; carbon as a coating layer is not only beneficial to improving the conductivity of the lithium iron borate phosphate positive electrode material, but also beneficial to improving the cycle stability.

[0053] Typically but not restrictively, in the chemical formula of the above-mentioned lithium iron borate phosphate positive electrode material, x is 1.02, 1.03, 1.04, 1.05 or a range value consisting of any two numerical values; y is 0.01, 0.02, 0.03, 0.04, 0.05 or a range value consisting of any two numerical values; z is 0.92, 0.93, 0.94, 0.95 or a range value consisting of any two numerical values; based on the mass of the lithium iron borate phosphate positive electrode material as 100%, the mass fraction of C is 1.00%, 1.02%, 1.05%, 1.08%, 1.10%, 1.12%, 1.15%, 1.18%, 1.20%, 1.25%, 1.30%, 1.35% or a range value consisting of any two numerical values.

[0054] Furthermore, in some embodiments, the D10 particle size of the lithium iron borate phosphate positive electrode material is ≤0.5 μm, the D50 particle size is ≤1.60 μm, and the D90 particle size is ≤19.00 μm.

[0055] In the present application, the D10 particle size refers to the particle size corresponding to when the cumulative particle size distribution of the lithium iron borate phosphate material reaches 10%, and its physical meaning is that particles with a particle size smaller than this value account for 10% of the total particles; the D50 particle size refers to the particle size corresponding to when the cumulative particle size distribution of the lithium iron borate phosphate material reaches 50%, and its physical meaning is that particles with a particle size smaller than this value account for 50% of the total particles; the D90 particle size refers to the particle size corresponding to when the cumulative particle size distribution of the lithium iron borate phosphate material reaches 90%, and its physical meaning is that particles with a particle size smaller than this value account for 90% of the total particles.

[0056] In the technical solution of the embodiment of the present application, the particle size of the lithium iron borate phosphate positive electrode material is more uniform and refined, which is more conducive to improving the capacity and cycle stability of the battery prepared using it as the positive electrode material.

[0057] Furthermore, in some embodiments, the pH value of the lithium iron borate phosphate positive electrode material is 8.50-9.00, such as 8.50, 8.60, 8.70, 8.80, 8.90, 9.00, etc., which makes it more conducive to homogenization in the subsequent preparation of positive electrode slurry, and is also more conducive to preparing positive electrode sheets with uniform dispersion of positive electrode materials and stable performance.

[0058] Furthermore, in some embodiments, the compaction density of the lithium borate iron phosphate cathode material is 2.35 g / mL to 2.50 g / mL, and the specific surface area is 10.1 m 2 / g-14.3m 2 / g, the powder resistivity is 4.0Ω.cm~13.0Ω.cm, its compaction density is higher, the specific surface area is larger, and the powder resistivity is lower, which is more conducive to improving the capacity of the battery formed by using the positive electrode material.

[0059] Typically but not limiting, the compaction density of the lithium borate iron phosphate positive electrode material is 2.35 g / mL, 2.40 g / mL, 2.45 g / mL, 2.50 g / mL or a range of any two values; its specific surface area is 10.1 m 2 / g, 10.5m 2 / g, 10.8m 2 / g, 11.0 m 2 / g, 11.2m 2 / g, 11.5m 2 / g, 11.8m 2 / g, 12.0m 2 / g, 12.5m 2 / g, 12.8m 2 / g, 13.0m 2 / g, 13.2m 2 / g, 13.5m 2 / g, 13.8m 2 / g, 14.0m 2 / g, 14.2m 2 / g, 14.3m 2 / g or a range value consisting of any two numerical values; its powder resistivity is 4.0Ω.cm, 4.5Ω.cm, 5.0Ω.cm, 5.5Ω.cm, 6.0Ω.cm, 8.0Ω.cm, 9.0Ω.cm, 10.0Ω.cm, 11.0 Ω.cm, 12.0Ω.cm, 13.0 Ω.cm or a range value consisting of any two numerical values.

[0060] Furthermore, in some embodiments, the lithium iron borate phosphate positive electrode material has iron dissolution of 3.0ppm to 10.0ppm, elemental iron of 0.01ppm to 0.05ppm, chloride ion of 40.0ppm to 80.0ppm, water content of 140ppm to 200ppm, free lithium of 140ppm to 200ppm, and magnetic impurity content of ≤1ppm, that is, the iron dissolution amount, elemental iron amount, chloride ion content, water content and free lithium content of the lithium iron borate phosphate positive electrode material provided in the present application are all at the ppm level in terms of mass concentration, and its structure is more stable and the impurity content is lower, thereby enabling it to have more excellent ionic conductivity and cycle stability.

[0061] In a second aspect, the present application provides a method for preparing a lithium borate iron phosphate positive electrode material, such as Figure 1 As shown, the preparation method includes the following steps: mixing a ferrous source, a trivalent titanium source, a carbon source, phosphoric acid, boric acid and a solvent to obtain a mixed slurry; preheating and drying the mixed slurry to obtain a pre-dried material; and calcining the pre-dried material to obtain a lithium borate iron phosphate positive electrode material.

[0062] The preparation method of the lithium borate iron phosphate positive electrode material provided in the present application adopts lithium source, ferrous source, trivalent titanium source, carbon source, phosphoric acid and boric acid as raw materials, which is more conducive to enhancing the driving force of the solid phase reaction, and is easier to form a eutectic body. Compared with the dry mixing and calcining process, the reaction temperature is further reduced, the particles are further refined, the capacity is further improved, and the production cost is further reduced. At the same time, the ionic radius of the trivalent titanium ion is larger, and more defects are formed, so that the ionic conductivity of the lithium borate iron phosphate positive electrode material is better and the capacity is higher; the boron element is doped in the form of borate ions and the molar mass of the borate is less than the molar mass of the phosphate, which is conducive to improving the capacity of the lithium borate iron phosphate positive electrode material; carbon as a coating layer is not only conducive to improving the conductivity of the lithium borate iron phosphate positive electrode material, but also conducive to improving the cycle stability.

[0063] Specifically, the preparation method of the lithium boron phosphate positive electrode material provided in the present application introduces boric acid which can serve as both a dopant and a flux, which can further reduce the calcination temperature and avoid the problems of increased particle size, iron phosphide and magnetic substance content, etc. of the lithium boron phosphate positive electrode material caused by high-temperature calcination.

[0064] Furthermore, the preparation method of the lithium iron borate phosphate positive electrode material provided by the present application reduces the steps of water slurrying, grinding and spray drying compared to the traditional process. According to the statistics of actual production, the cost (including labor, equipment depreciation, energy consumption, environmental protection, etc.) is about 2,500 yuan / ton. The preparation method of the lithium iron borate phosphate positive electrode material provided by the present application can save 2,500 yuan / ton in this step alone. According to the annual output of 100,000 tons of lithium iron borate phosphate positive electrode material, the cost can be saved by 250 million yuan / year.

[0065] Further, in some embodiments, the ferrous source is an aqueous ferrous source, the water-soluble ferrous source is a ferrous salt with volatile anions; the lithium source is a water-soluble lithium source, the water-soluble lithium source is a lithium salt with volatile anions, and the trivalent titanium source is a titanium salt with volatile anions. For example, the water-soluble ferrous source includes but is not limited to one or more of ferrous acetate and / or ferrous chloride, the water-soluble lithium salt includes but is not limited to one or more of lithium acetate and / or lithium chloride, and the water-soluble titanium source is a titanium halide, etc., so as to facilitate the full mixing of the water-soluble ferrous source, the water-soluble lithium salt and the water-soluble trivalent titanium source with the acid. At the same time, at high temperatures, volatile anions combine with hydrogen ions in the acid to form volatile low-boiling acid, and then the principle of preparing low-boiling acid with high-boiling acid is adopted. High-boiling acid such as boric acid and phosphoric acid is mixed with chloride ions, acetate ions and other ions to form low-boiling hydrogen chloride and acetic acid, while other ions combine together to form a composite lithium iron borate phosphate. The driving force of the solid-phase reaction is stronger and it is easier to form a eutectic body. Compared with the dry mixing and calcination process, the reaction temperature is further reduced, the particles are further refined, the capacity is further increased, and the production cost is further reduced.

[0066] Specifically, the completely solid-phase sintering method of dry mixing iron phosphate, lithium carbonate and carbon source and then calcining does not have the driving force of the present application (the principle of preparing low-boiling-point acid with high-boiling-point acid). At the same time, the raw material particles are large and the ion diffusion distance is long. High-temperature calcination requires a higher reaction temperature to achieve diffusion. Higher calcination temperatures will cause the particles to become larger and the capacity to be further reduced.

[0067] The preparation method of lithium boric phosphate positive electrode material provided by the present application introduces boric acid as both a dopant and a flux, which can further reduce the calcination temperature and avoid the problem of increased particle size, increased content of iron phosphide and magnetic substances in the lithium boric phosphate positive electrode material caused by high-temperature calcination. By using volatile anionic ferrous salts, volatile anionic lithium salts and volatile anionic titanium salts as raw materials, it is only necessary to use the higher volatility of low-boiling acid at a lower temperature (20°C-30°C lower than other dry mixing methods) to promote better material fusion and more refined particles, thereby further improving capacity.

[0068] Furthermore, in some embodiments, the trivalent titanium source used is a trivalent titanium salt with volatile anions. The trivalent titanium salt has a lower melting point (decomposition point) and can melt at a lower temperature, thereby enhancing the dispersion effect and making the trivalent titanium more uniformly doped in the lithium boron phosphate iron. The trivalent titanium source includes but is not limited to titanium trihalides, such as titanium trifluoride, titanium trichloride, titanium tribromide, etc., especially when the trivalent titanium source is titanium trichloride, it is possible to utilize the principle of preparing low-boiling-point acid with high-boiling-point acid to reduce the calcination reaction temperature, and it is possible to utilize the larger ionic radius of trivalent titanium ions to form more defects during the doping process, which is beneficial to enhancing the ionic conductivity of lithium ions. Therefore, its doping effect is better than that of tetravalent titanium (titanium dioxide, etc.); and titanium trichloride has a lower melting point (decomposition point), only 440°C. Compared with the high melting point of other traditional dopants such as titanium dioxide, titanium trichloride can be melted at a lower temperature, with better dispersion effect and more uniform doping, which is more conducive to improving the electrochemical properties of lithium borate iron phosphate positive electrode materials in terms of charge specific capacity, discharge specific capacity, etc.

[0069] Further, in some embodiments, the carbon source is a commonly used carbon source in the art. In order to facilitate the uniformity and conductivity of the mixing of the raw materials, the carbon source is preferably a water-soluble carbon source, and the water-soluble carbon source includes any one or more of ascorbic acid and / or citric acid, and is further preferably a mixture of ascorbic acid and citric acid. Preferably, the mass ratio of ascorbic acid to citric acid is (0.05-0.2): (0.92-0.95), such as the mass ratio between ascorbic acid and citric acid is 0.05: 0.92, 0.08: 0.92, 0.10: 0.92, 0.15: 0.92, 0.2: 0.92, 0.05: 0.95, 0.08: 0.95, 0.10: 0.95, 0.15: 0.95, 0.2: 0.95 or a range value composed of any two numerical values.

[0070] Further, in some embodiments, the solvent is selected from at least one of pure water, deionized water or distilled water.

[0071] Furthermore, in some embodiments, during the preparation of lithium iron borate phosphate positive electrode material, the molar ratio of iron in the ferrous source, titanium in the trivalent titanium source, lithium in the lithium source, carbon in the carbon source, phosphorus in the phosphoric acid solution and boron in the boric acid is 1: (0.01-0.05): (1.02-1.05): (0.36-1.32): (0.92-0.95): (0.05-0.15), so as to facilitate the preparation of improved capacity and cycle stability of the positive electrode material. For example, if the amount of iron in the ferrous source is 1 mol, the amount of trivalent titanium in the trivalent titanium source is 0.01 mol, 0.02 mol, 0.03 mol, 0.04 mol, 0.05 mol or a range consisting of any two values; the amount of lithium in the lithium source is 1.02 mol, 1.03 mol, 1.04 mol, 1.05 mol or a range consisting of any two values; the amount of carbon in the carbon source is 0.36 mol, 0.48 mol, 0.60 mol l, 0.72mol, 0.90mol, 1.08mol, 1.20mol, 1.32mol or a range consisting of any two values; the amount of phosphorus in phosphoric acid is 0.92mol, 0.93mol, 0.94mol, 0.95mol or a range consisting of any two values; the amount of boron in boric acid is 0.05mol, 0.08mol, 0.10mol, 0.12mol, 0.15mol or a range consisting of any two values.

[0072] Further, in some embodiments, in order to facilitate uniform mixing of phosphoric acid and other raw materials, phosphoric acid is first mixed with a solvent to form a phosphoric acid solution, and then the phosphoric acid solution is mixed with a lithium source, a ferrous source, a trivalent titanium source, and boric acid to form a mixed slurry. Alternatively, phosphoric acid and a solvent are provided simultaneously using a phosphoric acid solution. Further, it is preferred that the mass fraction of the phosphoric acid solution is 70%-80%, such as 70%, 72%, 75%, 78%, 80%, or a range value consisting of any two values.

[0073] Further, in some embodiments, in the preparation method of lithium boron phosphate positive electrode material, the sagger is used to charge, preheat and dry, enter the furnace, take out of the furnace, and pour the material, and the cycle is carried out in sequence to obtain the lithium boron phosphate positive electrode material. During the charging process, a metering module is provided below the charging station, and the metering module is electrically connected to the driving motor of the feeder and controls the driving motor to achieve accurate feeding. The sagger can be a graphite sagger.

[0074] Furthermore, in some embodiments, the mixed slurry is preheated and dried at 100°C-150°C to obtain a pre-dried material with a mass fraction of H2O less than or equal to 0.5%, so as to facilitate sufficient drying during the preheating and drying process and avoid reactions between the raw materials. At the same time, the water content of the dried material is controlled at ≤0.5wt%, so that the product generated during the subsequent calcination process is more dense and uniform, thereby further improving the density of the lithium borate iron phosphate positive electrode material.

[0075] Further, in some embodiments, the mixed slurry is prepared according to the following steps: phosphoric acid is mixed with a solvent to form a phosphoric acid solution with a mass fraction of 70% to 80%, and the mixture is set aside. A carbon source is first added to a mixture of a ferrous source, a trivalent titanium source, and a lithium source, and then the phosphoric acid solution and boric acid are added, and then the mixture is placed in a double cone mixer for mixing to obtain a mixed slurry.

[0076] In some embodiments, during the preheating and drying process, the exhaust fan is turned on to extract the waste gas, and the extracted waste gas is sprayed and absorbed with lithium hydroxide solution. The absorbed waste liquid is returned to the mixed slurry preparation process for recycling, so as to reduce energy consumption while reducing environmental pollution.

[0077] In some embodiments, the step of calcining the pre-dried material to obtain the lithium boron phosphate positive electrode material includes: under a protective atmosphere, the pre-dried material is calcined at a first calcination temperature for a first insulation time, and then at a second calcination temperature for a second insulation time to obtain the lithium boron phosphate positive electrode material; wherein the first calcination temperature is 120°C-150°C, the first insulation time is 2h-4h, the second calcination temperature is 600°C-700°C, and the second insulation time is 4h-6h. By controlling the first calcination temperature, the first insulation time, the second calcination temperature and the second insulation time, it is more conducive to preparing a lithium boron phosphate positive electrode material with finer and more uniform particles, more regular morphology, and higher density, and it is also conducive to further saving energy consumption and reducing production costs.

[0078] Typically but not limiting, the first calcination temperature is 120°C, 130°C, 140°C, 150°C or a range consisting of any two values; the first insulation time is 2h, 2.5h, 3h, 3.5h, 4h or a range consisting of any two values, the second calcination temperature is 600°C, 620°C, 650°C, 680°C, 700°C or a range consisting of any two values, and the second insulation time is 4h, 4.5h, 5h, 5.5h, 6h or a range consisting of any two values.

[0079] In some embodiments, during the calcination process, a protective gas is introduced to form a protective atmosphere to maintain the oxygen volume content below 5 ppm during the calcination process to further reduce the introduction of impurities. The protective gas includes but is not limited to any one of nitrogen, argon or helium.

[0080] In some embodiments, the calcination process is performed in a roller hearth furnace. During the calcination process, a protective gas is introduced to form a protective atmosphere, and the oxygen volume content in the roller hearth furnace is maintained below 5 ppm to further reduce the introduction of impurities.

[0081] In some embodiments, the pre-dried material is heated from room temperature to a first calcination temperature at a first heating rate for a first insulation time, then heated from the first calcination temperature to a second calcination temperature at a second heating rate for a second insulation time, and then cooled to a material temperature less than or equal to 100°C to obtain a lithium iron borate phosphate positive electrode material; wherein the first heating rate is 20°C / h-30°C / h, and the second heating rate is 50°C / h-100°C / h, so as to make the obtained positive electrode material denser, with fewer defects and more regular morphology.

[0082] Typically but not limiting, the first heating rate is 20°C / h, 22°C / h, 25°C / h, 28°C / h, 30°C / h or a range consisting of any two values, and the second heating rate is 50°C / h, 55°C / h, 60°C / h, 70°C / h, 80°C / h, 90°C / h, 95°C / h, 100°C / h or a range consisting of any two values.

[0083] In some embodiments, the calcined material is crushed, screened, iron-removed and packaged to obtain a lithium boric iron phosphate positive electrode material. The screening is performed using a 100-200 mesh sieve, and the iron is removed until the magnetic impurity content of the anhydrous iron phosphate is less than 1 ppm before vacuum packaging. The vacuum packaging is performed under constant temperature (25±5°C) and constant humidity (≤10%) conditions.

[0084] In some embodiments, the calcined material is transported to a jet mill through a pipeline conveying system, and then screened by an ultrasonic vibration screen, iron removed by an electromagnetic iron remover, and vacuum packaged in a constant temperature and humidity room to obtain a lithium boric iron phosphate positive electrode material. The temperature in the constant temperature and humidity room is 25±5°C, and the humidity is ≤10%.

[0085] In order to further reduce environmental pollution, in some embodiments, the waste gas generated during the calcination process is introduced into a spray absorption tower through an induced draft fan and absorbed by pure water. The absorption liquid reacts with the iron powder, and the obtained ferrous solution is concentrated and crystallized and then returned to the preparation step of obtaining the mixed slurry as a raw material to further reduce energy consumption.

[0086] In a third aspect, an embodiment of the present application provides a positive electrode plate, which includes the lithium iron borate phosphate positive electrode material provided in the first aspect.

[0087] In this embodiment, the positive electrode plate includes the above-mentioned lithium iron borate phosphate positive electrode material, which not only has higher compaction density and capacity, but also has better ion conductivity and cycle stability, and has broader application prospects in the field of secondary batteries.

[0088] In a fourth aspect, an embodiment of the present application provides a secondary battery, which includes the lithium iron borate phosphate positive electrode material provided in the first aspect or the positive electrode plate provided in the third aspect.

[0089] In this embodiment, the secondary battery includes the above-mentioned positive electrode plate, so it not only has a high capacity but also has better ion conductivity and cycle stability.

[0090] In a fifth aspect, an embodiment of the present application provides an electrical device, such as a vehicle, comprising the lithium iron borate phosphate positive electrode material provided in the first aspect, the positive electrode plate provided in the third aspect, or the secondary battery provided in the fourth aspect.

[0091] In this embodiment, the electric device includes the above-mentioned secondary battery, so it has excellent cycle stability. Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and cannot be understood as limitations on this application. If the specific technology or conditions are not specified in the embodiment, the technology or conditions described in the literature in this field or the product instructions are used. The reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained commercially.

[0092] Example 1

[0093] This embodiment provides a lithium iron borate phosphate positive electrode material, which is prepared according to the following steps:

[0094] (1) Ferrous acetate, titanium trichloride, lithium acetate, ascorbic acid, citric acid, 80% by mass phosphoric acid solution and boric acid are placed in an oblique mixer and mixed to obtain a mixed slurry; wherein the molar ratio of ferrous acetate, titanium trichloride, lithium acetate, ascorbic acid, citric acid, phosphoric acid and boric acid is 1:0.03:1.04:0.015:0.12:0.94:0.1, and during the mixing process, grinding balls are added into the oblique mixer, the inside of the grinding balls is stainless steel and the outside is wrapped with polyurethane, the diameter of the grinding balls is 5 cm, the rotation speed is 8 r / min, the filling amount is 60% of the effective volume of the mixer, and the mixing time is 50 min.

[0095] (2) The mixed slurry is added into a graphite sagger through a feeder using a screw feeder, and then preheated and dried until the free water content of the mixed slurry is less than 0.5wt%, thereby obtaining a predried material; wherein the preheated and dried temperature is 120°C, and at the same time, an exhaust fan is turned on to extract the waste gas therein, and the extracted waste gas is sprayed and absorbed by a lithium hydroxide solution, and the obtained absorbed waste liquid is returned to step (1) for recycling.

[0096] (3) The pre-dried material is placed in a roller furnace for calcination. During the calcination process, the temperature is first raised to 135°C at a rate of 25°C / h, and the temperature is kept at this temperature for 4 hours. Then, the temperature is raised to 650°C at a rate of 80°C / h, and the temperature is kept at this temperature for 5 hours. Then, the temperature is lowered to ≤100°C before discharging the material. During the calcination process, nitrogen is introduced into the roller furnace to maintain the oxygen volume content in the roller furnace below 5ppm. The waste gas generated by the calcination is introduced into the spray absorption tower through an induced draft fan and absorbed by pure water. The absorption liquid is added with iron powder for reaction. The obtained ferrous solution is concentrated and crystallized and then returned to step (1) for recycling. The calcined material is transported to the air flow mill through a pipeline conveying system, sieved by an ultrasonic vibration screen, and vacuum packaged in a constant temperature and humidity room to obtain a lithium boric acid iron phosphate positive electrode material; wherein, the sieving is carried out by a 150-mesh ultrasonic vibration screen, and the temperature in the constant temperature and humidity room is 25±5°C and the humidity is ≤10%.

[0097] In this embodiment, loading, preheating and drying, furnace entry, furnace exit and material unloading are carried out in a cycle in sequence through a return line. During the loading process, a metering module is arranged under the loading station. The accuracy of the metering module is 0.5%. The metering module is electrically connected to the driving motor of the feeder and controls the driving motor to achieve precise feeding.

[0098] Example 2

[0099] This embodiment provides a lithium iron borate phosphate positive electrode material, which is prepared according to the following steps:

[0100] (1) Ferrous chloride, titanium trichloride, lithium chloride, ascorbic acid, citric acid, a 70% by mass phosphoric acid solution and boric acid are placed in an oblique mixer and mixed to obtain a mixed slurry; wherein the molar ratio of ferrous chloride, titanium trichloride, lithium chloride, ascorbic acid, citric acid, phosphoric acid and boric acid is 1:0.05:1.05:0.02:0.2:0.95:0.15, and during the mixing process, grinding balls are added into the double cone mixer, the inside of the grinding balls is stainless steel and the outside is wrapped with polyurethane, the diameter of the grinding balls is 3 cm, the rotation speed is 5 r / min, the filling amount is 50% of the effective volume of the mixer, and the mixing time is 30 min.

[0101] (2) The mixed slurry is added into a graphite sagger through a feeder using a screw feeder, and then the preheating and drying is stopped when the free water content of the mixed slurry is lower than 0.5wt%, thereby obtaining a predried material; wherein the preheating and drying temperature is 150°C, and at the same time, an exhaust fan is turned on to extract the waste gas therein, and the extracted waste gas is sprayed and absorbed by a lithium hydroxide solution, and the obtained absorption waste liquid is returned to step (1) for recycling.

[0102] (3) The pre-dried material is placed in a roller furnace for calcination. During the calcination process, the temperature is first raised to 150°C at a rate of 20°C / h, kept at this temperature for 4 hours, then raised to 700°C at a rate of 100°C / h, kept at this temperature for 4 hours, and then cooled to a material temperature of ≤100°C before discharging. During the calcination process, nitrogen is introduced into the roller furnace to maintain the oxygen volume content in the roller furnace below 5ppm. The waste gas generated by the calcination is introduced into a spray absorption tower through an induced draft fan and absorbed by pure water. The absorption liquid is added with iron powder for reaction. The obtained ferrous solution is concentrated and crystallized and then returned to step (1) for recycling. The calcined material is transported to a jet mill through a pipeline conveying system, and then screened through an ultrasonic vibration screen and vacuum packaged in a constant temperature and humidity room to obtain a lithium boric iron phosphate positive electrode material; wherein, the screening is performed using a 100-mesh ultrasonic vibration screen, and the iron is removed until the magnetic impurity content of the anhydrous iron phosphate is less than 1ppm before vacuum packaging. The temperature in the constant temperature and humidity room is 25±5°C, and the humidity is ≤10%.

[0103] This embodiment uses a return line to carry out loading, preheating and drying, furnace entry, furnace exit, and material dumping in a cycle. During the loading process, a metering module is provided under the loading station. The metering module is electrically connected to the driving motor of the feeder and controls the driving motor to achieve precise feeding.

[0104] Example 3

[0105] This embodiment provides a lithium iron borate phosphate positive electrode material, which is prepared according to the following steps:

[0106] (1) Ferrous acetate, titanium trichloride, lithium chloride, ascorbic acid, citric acid, 80% by mass phosphoric acid solution and boric acid are placed in an oblique mixer and mixed to obtain a mixed slurry, wherein the molar ratio of ferrous acetate, titanium trichloride, lithium chloride, ascorbic acid, citric acid, phosphoric acid and boric acid is 1:0.01:1.02:0.01:0.05:0.92:0.1, and then placed in a double cone mixer for mixing; and during the mixing process, grinding balls are added into the double cone mixer, the inside of the grinding balls is stainless steel and the outside is wrapped with polyurethane, the diameter of the grinding balls is 3 cm, the rotation speed is 5 r / min, the filling amount is 50% of the effective volume of the mixer, and the mixing time is 30 min.

[0107] (2) The mixed slurry is added into a graphite sagger through a feeder using a screw feeder, and then the mixed slurry is preheated and dried until the free water content of the mixed slurry is less than 0.5wt%, thereby obtaining a pre-dried material; wherein the preheating and drying temperature is 100°C, and at the same time, an exhaust fan is turned on to extract the waste gas therein, and the extracted waste gas is sprayed and absorbed by a lithium hydroxide solution, and the obtained absorption waste liquid is returned to step (1) for recycling.

[0108] (3) The pre-dried material is placed in a roller furnace for calcination. During the calcination process, the temperature is first raised to 120°C at a rate of 30°C / h, kept at this temperature for 2h, then raised to 600°C at a rate of 50°C / h, kept at this temperature for 6h, and then cooled to a material temperature of ≤100°C for discharge. During the calcination process, nitrogen is introduced into the roller furnace to maintain the oxygen volume content in the roller furnace below 5ppm. The waste gas generated by the calcination is introduced into the spray absorption tower through an induced draft fan and absorbed by pure water. The absorption liquid is added with iron powder for reaction. The obtained ferrous solution is concentrated and crystallized and then returned to step (1) for recycling. The calcined material is transported to a jet mill through a pipeline conveying system, sieved by an ultrasonic vibrating screen, and vacuum packaged in a constant temperature and humidity room to obtain a lithium boric iron phosphate positive electrode material; wherein, the sieving is carried out using a 200-mesh ultrasonic vibrating screen, and the iron is removed until the magnetic impurity content of the anhydrous iron phosphate is less than 1ppm before vacuum packaging. The temperature in the constant temperature and humidity room is 25±5°C and the humidity is ≤10%.

[0109] This embodiment uses a return line to carry out loading, preheating and drying, furnace entry, furnace exit, and material dumping in a cycle. During the loading process, a metering module is provided under the loading station. The metering module is electrically connected to the driving motor of the feeder and controls the driving motor to achieve precise feeding.

[0110] Example 4

[0111] This embodiment provides a lithium iron borate phosphate positive electrode material, which is prepared according to the following steps:

[0112] (1) Ferrous chloride, titanium trichloride, lithium acetate, ascorbic acid, citric acid, a phosphoric acid solution with a mass fraction of 77%, and boric acid are placed in an oblique mixer and mixed to obtain a mixed slurry; wherein the molar ratio of ferrous chloride, titanium trichloride, lithium acetate, ascorbic acid, citric acid, phosphoric acid, and boric acid is 1:0.03:1.02:0.02:0.1:0.95:0.1, and during the mixing process, grinding balls are added into the oblique mixer, the inside of the grinding balls is stainless steel, the outside is wrapped with polyurethane, the diameter of the grinding balls is 6 cm, the rotation speed is 8 r / min, the filling amount is 55% of the effective volume of the mixer, and the mixing time is 40 min.

[0113] (2) The mixed slurry is added into a graphite sagger through a feeder using a screw feeder, and then preheated and dried until the free water content of the mixed slurry is less than 0.5wt%, thereby obtaining a predried material; wherein the preheated and dried temperature is 140°C, and at the same time, an exhaust fan is turned on to extract the waste gas therein, and the extracted waste gas is sprayed and absorbed by a lithium hydroxide solution, and the obtained absorbed waste liquid is returned to step (1) for recycling.

[0114] (4) The pre-dried material is placed in a roller furnace for calcination. During the calcination process, the temperature is first raised to 130°C at a rate of 22°C / h, and the temperature is kept at this temperature for 3h, then the temperature is raised to 640°C at a rate of 65°C / h, and the temperature is kept at this temperature for 5h, and then the temperature is lowered to a material temperature of ≤100°C for discharge. During the calcination process, nitrogen is introduced into the roller furnace to maintain the oxygen volume content in the roller furnace below 5ppm. The waste gas generated by the calcination is introduced into the spray absorption tower through an induced draft fan and absorbed by pure water. The absorption liquid is added with iron powder for reaction. The obtained ferrous solution is concentrated and crystallized and then returned to step (1) for recycling. The calcined material is transported to the air flow mill through a pipeline conveying system, sieved by an ultrasonic vibration screen, and vacuum packaged in a constant temperature and humidity room to obtain a lithium boric iron phosphate positive electrode material; wherein, a 150-mesh sieve is used for sieving, and the iron is removed until the magnetic impurity content of the anhydrous iron phosphate is less than 1ppm before vacuum packaging. The temperature in the constant temperature and humidity room is 25±5°C and the humidity is ≤10%.

[0115] Example 5

[0116] The difference between this embodiment and embodiment 1 is that ferrous sulfate is used instead of ferrous acetate as the water-soluble ferrous source, and lithium nitrate is used instead of lithium acetate as the water-soluble lithium source.

[0117] Example 6

[0118] The difference between this embodiment and embodiment 1 is that ascorbic acid is not added, but the molar number of citric acid is the same as the sum of the molar numbers of ascorbic acid and citric acid in embodiment 1.

[0119] Example 7

[0120] The difference between this embodiment and embodiment 1 is that citric acid is not added, but the molar number of ascorbic acid is the same as the sum of the molar numbers of ascorbic acid and citric acid in embodiment 1.

[0121] Example 8

[0122] The difference between this embodiment and embodiment 1 is that titanium tribromide is used instead of titanium trichloride as the titanium source.

[0123] Example 9

[0124] The difference between this embodiment and embodiment 1 is that the molar ratio of ferrous acetate, titanium trichloride, lithium acetate, ascorbic acid, citric acid, phosphoric acid and boric acid is 1:0.01:1.02:0.01:0.05:0.92:0.05.

[0125] Example 10

[0126] The difference between this comparative example and Example 1 is that the molar ratio of ferrous acetate, titanium trichloride, lithium acetate, ascorbic acid, citric acid, phosphoric acid and boric acid is 1:0.03:1.04:0.015:0.12:0.84:0.2.

[0127] Embodiment 11

[0128] The difference between this comparative example and Example 1 is that the molar ratio of ferrous acetate, titanium trichloride, lithium acetate, ascorbic acid, citric acid, phosphoric acid and boric acid is 1:0.15:1.04:0.015:0.12:0.84:0.2.

[0129] Comparative Example 1

[0130] The difference between this comparative example and Example 1 is that no boric acid is added, but the molar number of phosphoric acid is the same as the sum of the molar numbers of phosphoric acid and boric acid in Example 1.

[0131] Comparative Example 2

[0132] The difference between this comparative example and Example 1 is that ferrous acetate is replaced by ferrous phosphate in an equal molar amount, lithium acetate is replaced by lithium carbonate in an equal molar amount, and phosphoric acid is not added.

[0133] Comparative Example 3

[0134] The difference between this comparative example and Example 1 is that titanium dioxide is used to replace titanium trichloride as the titanium source, and the titanium dioxide is in rutile phase, with a primary particle size of about 30 nm and a BET value of 30 nm. 2 / g.

[0135] Comparative Example 4

[0136] The difference between this comparative example and Example 1 is that no titanium trichloride doping is added.

[0137] Test Method

[0138] 1. The positive electrode materials provided in the above embodiments and comparative examples were respectively subjected to morphology inspection using a scanning electron microscope.

[0139] 2. The content of each element, compacted density, BET, D10, D50, D90, powder resistivity, iron dissolution, elemental iron content, magnetic foreign matter content, chloride ion content, moisture content, free lithium content and pH of the positive electrode materials provided in the embodiments and comparative examples were measured respectively. The results are shown in Tables 1 and 2 below.

[0140] Among them, (1) determination of the content of each element in the positive electrode material: determination by ICP-OES spectrometer;

[0141] (2) The test method for compaction density is: refer to GB / T 24533, Determination of compaction density of powders;

[0142] (3) The BET test method is: refer to GB / T 19587, gas adsorption BET method for determining the specific surface area of ​​solid substances;

[0143] (4) The determination method of D10, D50 and D90 is as follows: refer to GB / T 19077, particle size analysis laser diffraction method;

[0144] (5) The powder resistivity was measured by a four-probe method at a pressure of 10 MPa.

[0145] (6) The determination method of iron dissolution is as follows: 1 g of the sample to be tested is added to 100 mL of a 0.1 mol / L hydrogen fluoride-ethanol solution, stirred and dissolved at 45°C for 30 min, and then filtered. The iron content of the obtained filtrate is measured, which is the iron dissolution amount;

[0146] (7) The method for determining the elemental iron content is: refer to the potassium dichromate titration method in GB / T 223.7-2002;

[0147] (8) The method for determining the content of magnetic foreign matter is as follows: weigh 100 g of the material, pour it into a plastic bottle with a lid, add 1000 g of pure water, and then add an 8000 GS magnet, with the outside of the magnet protected by polytetrafluoroethylene, then close the lid tightly, place the plastic bottle horizontally and rotate the plastic bottle at a speed of 10-20 r / min, rotate for 30-45 minutes, stop rotating, take out the magnet, add 1000 g of pure water, put it into the plastic bottle, close the lid tightly, place the plastic bottle horizontally and rotate the plastic bottle at a speed of 10-20 r / min, rotate for 5-10 minutes, stop rotating, take out the magnet, add aqua regia to dissolve, measure the solution with ICP, make the volume constant, measure the nickel, chromium, copper, zinc and iron content therein, calculate the total mass of nickel, chromium, copper, zinc and iron, and divide it by the weight of the material to obtain the magnetic foreign matter content of the material.

[0148] (9) Determination of moisture content: GB / T 6283, Determination of moisture content in chemical products - Karl Fischer method (general method);

[0149] (10) Determination of chloride ion content: GB / T23273.6-2009, ion selective electrode method;

[0150] (11) Determination of free lithium content: SJT 11794-2021, automatic potentiometric titration method;

[0151] (12) The pH value was determined according to GB / T 9724, General rules for determination of pH value of chemical reagents.

[0152] Figure 2 This is a SEM image of the lithium iron borate phosphate positive electrode material provided in Example 1; Figure 3 This is a SEM image of the lithium iron borate phosphate positive electrode material provided in Example 2; Figure 4 This is a SEM image of the lithium iron borate phosphate positive electrode material provided in Example 3; Figure 5 This is a SEM image of the lithium borate iron phosphate cathode material provided in Comparative Example 2. Figure 2-Figure 5 It can be seen that compared with the positive electrode material formed by the traditional dry mixing and calcination process in Comparative Example 2, the lithium iron borate phosphate positive electrode material particles provided in Examples 1-3 of the present application have better dispersibility, higher sphericity, more regular morphology, higher particle size consistency and reasonable size matching, so that the product has a good compaction density.

[0153] Table 1

[0154] Li(%) Fe(%) P(%) B C(%) Ti(ppm) D10(μm) D50(μm) D90(μm) Example 1 4.45 34.68 18.44 0.69% 1.32 7435 0.31 1.32 9.46 Example 2 4.42 34.54 18.32 0.98% 1.31 7378 0.35 1.29 11.24 Example 3 4.39 34.73 18.37 0.76% 1.01 1759 0.48 1.59 18.45 Example 4 4.35 34.69 18.54 0.73% 1.21 5325 0.42 1.51 9.21 Example 5 4.44 34.65 18.47 0.68% 1.31 7421 0.32 1.35 9.41 Example 6 4.44 34.64 18.43 0.67% 1.39 7412 0.28 1.32 9.38 Example 7 4.46 34.69 18.49 0.68% 1.27 7448 0.29 1.38 9.78 Example 8 4.44 34.56 18.37 0.64% 1.31 7328 0.32 1.28 9.38 Example 9 4.42 34.75 18.52 0.35% 1.31 7511 0.32 1.26 9.98 Example 10 4.46 34.43 18.12 1.45% 1.31 7413 0.35 1.39 9.59 Embodiment 11 4.35 34.43 18.12 1.47% 1.32 36574 0.52 1.52 19.45 Comparative Example 1 4.42 34.26 19.12 2.1ppm 1.30 7235 0.33 1.25 9.98 Comparative Example 2 4.48 34.89 18.15 0.65% 1.35 7498 0.36 1.21 13.56 Comparative Example 3 4.42 34.35 18.27 0.67% 1.30 7449 0.32 1.39 9.59 Comparative Example 4 4.48 34.97 18.65 0.71% 1.34 13.8 0.76 1.76 21.78

[0155] As can be seen from Table 1, the D10 particle size of the lithium iron borate phosphate positive electrode material provided in Examples 1-11 of the present application is ≤0.5μm, the D50 particle size is ≤1.60μm, and the D90 particle size is ≤19.45μm. The lithium iron borate phosphate positive electrode material provided in Examples 1-11 of the present application is cation-doped with titanium and anion-doped with boron, and the particle size is more uniform, which is more conducive to improving the compaction density of the positive electrode sheet prepared as the positive electrode material.

[0156] Table 2

[0157]

[0158]

[0159] It can be seen from Table 2 that the compaction density of the lithium borate iron phosphate positive electrode material provided in Examples 1-11 of the present application is 2.35-2.52 m 2 / g, specific surface area is 8.6m 2 / g-14.3m 2 / g, and the powder resistivity is 4.0Ω.cm~13.0Ω.cm, which is more conducive to improving the capacity of the battery formed by using the lithium iron borate phosphate positive electrode material.

[0160] In addition, it can be seen from Table 2 that the lithium borate iron phosphate positive electrode material provided in Examples 1-9 of the present application has a molecular formula satisfying Li x FeTi y P z B w O (4z+3w+2y) / C, wherein x, y, z and w are all non-zero positive numbers, 1.02≤x≤1.05, 0.01≤y≤0.05, 0.92≤z≤0.95, 0.05≤w≤0.15, the iron dissolution is 3.0ppm~10.0ppm, the elemental iron is 0.01ppm~0.05ppm, the chloride ion is 40.0ppm~80.0ppm, the water content is 280ppm~350ppm, the free lithium is 140ppm~200ppm, the magnetic impurity content is ≤1ppm, the magnetic substance content is low, which is more conducive to improving the capacity and rate performance of the lithium borate iron phosphate positive electrode material.

[0161] The lithium boron phosphate positive electrode material provided in Examples 10-11 of the present application has an excessively high boron content, which results in an excessively high iron content in the element. The self-discharge of the battery cell made of the lithium boron phosphate positive electrode material is large and the K value is high, which affects the product performance of the secondary battery manufactured.

[0162] Performance test of positive electrode and secondary battery

[0163] The positive electrode materials provided in the embodiment and the comparative example are respectively prepared into positive electrode sheets and assembled into secondary batteries. The specific process is as follows: the positive electrode materials provided in the embodiment and the comparative example are respectively mixed with conductive carbon black (SP) conductive agent, polyvinylidene fluoride (PVDF), and N-methylpyrrolidone (NMP) by a high-speed mixer, wherein the mass ratio of the positive electrode material, SP conductive agent, and PVDF provided in the embodiment or the comparative example is 90:5:5. Then, an automatic coating machine is used to coat the aluminum foil, the coated aluminum foil is dried in an oven and rolled according to the required compaction density, cut into discs of the required size, weighed, and then dried again to obtain the positive electrode sheet; and the lithium sheet is used as the negative electrode sheet, and the positive electrode shell, the negative electrode shell, the positive electrode sheet, the lithium sheet, the diaphragm, and the electrolyte are assembled into a button battery as required; the button battery is hung on the battery test system and left to stand for testing.

[0164] The assembled button batteries were placed on a Blue Power battery testing system (Wuhan Blue Power CT2001A battery testing system) for testing. The test temperature was 25°C, the charge limit voltage was 3.75V, the discharge termination voltage was 2.0V, and they were charged and discharged at 0.1C and 10C rate currents, respectively, to obtain 0.1C first discharge specific capacity, 0.1C first discharge specific capacity, and 10C first discharge specific capacity. The 1C discharge specific capacity of the assembled button batteries at -20°C was further tested and the percentage of the 1C discharge specific capacity at 25°C was calculated to obtain the -20°C capacity retention rate. The results are shown in Table 3 below.

[0165] Table 3

[0166]

[0167]

[0168] It can be seen from the data in Table 3 that the lithium iron borate phosphate positive electrode material provided in the embodiment of the present application is cation-doped with trivalent titanium and anion-doped with boron, and is coated with carbon, so that the lithium iron borate phosphate positive electrode material not only has a higher charge specific capacity and discharge specific capacity, but also has a higher capacity retention rate at -20°C, and has strong low temperature resistance.

[0169] From the comparison between Examples 1-9 and Examples 10-11, it can be seen that the molar ratio of iron, titanium, lithium, carbon, phosphorus and boron in the lithium iron borate phosphate positive electrode material provided in the embodiments of the present application is maintained at 1: (0.01-0.05): (1.02-1.05): (0.06-0.22): (0.92-0.95): (0.05-0.15), which is beneficial to the improvement of the charging specific capacity, discharge specific capacity, -20°C capacity retention rate and other aspects of the lithium iron borate phosphate positive electrode material.

[0170] From the comparison between Examples 1-9 and Comparative Example 1, it can be seen that the anion doping of borate is beneficial to the improvement of the electrical properties of the lithium iron borate phosphate positive electrode material; from the comparison between Examples 1-9 and Comparative Example 2, it can be seen that the electrical properties of the lithium iron borate phosphate positive electrode material prepared by replacing ferrous acetate with lithium phosphate and replacing lithium acetate with lithium carbonate are significantly reduced, indicating that compared with the traditional dry mixing and calcination, the method for preparing the lithium iron borate phosphate positive electrode material provided in the present application, the prepared lithium iron borate phosphate positive electrode material has significantly improved electrical properties.

[0171] From the comparison between Examples 1-9 and Comparative Example 3, it can be seen that compared with the use of tetravalent titanium ions for cation doping, the lithium iron borate phosphate positive electrode material provided in the present application uses trivalent titanium ions for cation doping, which has obvious improvements in charge specific capacity, discharge specific capacity and -20°C capacity retention rate.

[0172] From the comparison between Examples 1-11 and Comparative Example 4, it can be seen that compared with the lithium iron borate phosphate positive electrode material prepared without titanium doping, the lithium iron borate phosphate positive electrode material provided in the present application uses trivalent titanium ions for cation doping, which has obvious improvements in charge specific capacity, discharge specific capacity and -20°C capacity retention rate.

[0173] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A lithium iron borate phosphate positive electrode material, characterized in that: The general formula of the lithium borate iron phosphate positive electrode material is Li x FeTi y P z B w O (4z+3w+2y) / C, wherein x, y, z and w are all non-zero positive numbers, 1.02≤x≤1.05, 0.01≤y≤0.05, 0.92≤z≤0.95, 0.05≤w≤0.15, and the mass fraction of carbon element in the boric acid phosphate positive electrode material is 1.00%-1.35%.

2. The lithium borate iron phosphate positive electrode material according to claim 1, characterized in that: The D10 particle size of the lithium boron iron phosphate material is ≤0.50 μm, the D50 particle size is ≤1.60 μm, and the D90 particle size is ≤19.00 μm.

3. The lithium borate iron phosphate positive electrode material according to claim 1, characterized in that: The compaction density of the lithium borate iron phosphate positive electrode material is 2.35 g / mL to 2.50 g / mL, and the specific surface area is 10.1 m 2 / g~14.3m 2 / g, powder resistivity is 4.0Ω.cm~13.0Ω.cm.

4. The lithium boron phosphate positive electrode material according to any one of claims 1 to 3, characterized in that: The lithium borate iron phosphate positive electrode material has an iron dissolution of 3.0ppm to 10.0ppm, an elemental iron of 0.01ppm to 0.05ppm, a chloride ion of 40.0ppm to 80.0ppm, a water content of 280ppm to 350ppm, a free lithium of 140ppm to 200ppm, and a magnetic impurity content of ≤1ppm.

5. A method for preparing a lithium boron phosphate positive electrode material, characterized in that: The preparation method comprises the following steps: Mixing a lithium source, a ferrous source, a trivalent titanium source, a carbon source, phosphoric acid, boric acid and a solvent to obtain a mixed slurry; Preheating and drying the mixed slurry to obtain a pre-dried material; The pre-dried material is calcined to obtain the lithium borophosphate iron positive electrode material.

6. The method for preparing the lithium boron phosphate positive electrode material according to claim 5, characterized in that: The molar ratio of the iron element in the ferrous source, the titanium element in the trivalent titanium source, the lithium element in the lithium source, the carbon element in the carbon source, the phosphorus element in the phosphoric acid and the boron element in the boric acid is 1: (0.01-0.05): (1.02-1.05): (0.36-1.32): (0.92-0.95): (0.05-0.15).

7. The method for preparing the lithium boron phosphate positive electrode material according to claim 6, characterized in that: The ferrous source includes at least one of ferrous acetate and / or ferrous chloride; And / or, the lithium source includes at least one of lithium chloride and / or lithium acetate; and / or, the trivalent titanium source comprises titanium trihalide, preferably titanium trichloride; And / or, the step of mixing the lithium source, the ferrous source, the trivalent titanium source, the carbon source, phosphoric acid, boric acid and the solvent comprises: mixing the phosphoric acid with the solvent to form a phosphoric acid solution, and then mixing the phosphoric acid solution with the lithium source, the ferrous source, the trivalent titanium source and the boric acid, preferably the mass fraction of the phosphoric acid in the phosphoric acid solution is 70%-80%; And / or, the carbon source includes at least one of ascorbic acid and / or citric acid, and the carbon source is preferably a mixture of ascorbic acid and citric acid, and the mass ratio of ascorbic acid to citric acid is (0.05-0.2):(0.92-0.95).

8. The method for preparing the lithium boron phosphate positive electrode material according to claim 5, characterized in that: Preheating and drying the mixed slurry at 100° C.-150° C. to obtain a predried material having a mass fraction of H2O less than or equal to 0.5%; And / or, the step of calcining the pre-dried material to obtain the lithium borophosphate iron positive electrode material comprises: In a protective atmosphere, the pre-dried material is calcined at a first calcination temperature for a first insulation time, and then calcined at a second calcination temperature for a second insulation time to obtain the lithium boric phosphate positive electrode material; Wherein, the first calcination temperature is 120°C-150°C, and the first insulation time is 2h-4h; The second calcination temperature is 600° C.-700° C., and the second insulation time is 4 h-6 h.

9. A positive electrode sheet, characterized in that: The positive electrode plate comprises the lithium iron borate phosphate positive electrode material according to any one of claims 1 to 4 or the lithium iron borate phosphate positive electrode material obtained by the preparation method of the lithium iron borate phosphate positive electrode material according to any one of claims 5 to 8.

10. A secondary battery, characterized in that: The secondary battery comprises the lithium iron borate phosphate positive electrode material according to any one of claims 1 to 4 or the positive electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Polymer composite lithium iron phosphate positive electrode material and preparation method thereof

    CN112563472A

  • High-compaction lithium iron phosphate positive electrode material, preparation method thereof, positive electrode of high-compaction lithium iron phosphate positive electrode material and battery

    CN114759178A

  • Doping modified lithium iron phosphate material, preparation method thereof and lithium ion battery

    CN116053467A

  • High-tap-density lithium iron phosphate positive electrode material as well as preparation method and application thereof

    CN116565180A

  • Positive electrode material, preparation method and application

    CN117954622A

Cited By

  • Positive electrode material, and preparation method therefor and use thereof

    EP4819234A4

  • Positive electrode material, and preparation method therefor and use thereof

    WO2026174519A1